2015
DOI: 10.1007/10_2015_308
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes for Synthetic Biology of Ambroxide-Related Diterpenoid Fragrance Compounds

Abstract: Ambrox and related ambroxides are highly priced in the fragrance industry, and valued for their delicate odor and fixative properties. Historically, ambrox was obtained from ambergris, a waxy excretion produced by sperm whales, now an endangered species. Synthetic ambroxides have replaced ambergris in perfume manufacture. Plant labdane diterpenoids can serve as starting material for ambroxide synthesis. Among these, the diterpene alcohol sclareol is the major industrial precursor obtained from cultivated clary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 95 publications
(188 reference statements)
0
27
0
Order By: Relevance
“…Previously characterized plant class II diTPSs include enzymes for the formation of ent ‐CPP, syn ‐CPP, normal CPP [i.e. (+)‐CPP], LPP and peregrinol diphosphate (for review see Zerbe and Bohlmann, ).…”
Section: Resultsmentioning
confidence: 99%
“…Previously characterized plant class II diTPSs include enzymes for the formation of ent ‐CPP, syn ‐CPP, normal CPP [i.e. (+)‐CPP], LPP and peregrinol diphosphate (for review see Zerbe and Bohlmann, ).…”
Section: Resultsmentioning
confidence: 99%
“…Beyond application in the perfume industry, animal studies have also demonstrated the potential anti-nociceptive ( Taha, 1992 ) and aphrodisiac ( Taha et al, 1995 ) properties of (+)-ambrein as well as possible effects on the cardiovascular system ( Raza et al, 1999 ) and on smooth muscle response ( Taha et al, 1998 ). As the natural ambergris supply is highly limited, total or partial syntheses (reviewed by Zerbe and Bohlmann, 2015 ) have been developed for production of (+)-ambrein, (-)-ambrox and related compounds. A recent study by Ueda et al (2013) described the possibility to produce (+)-ambrein from squalene applying only two enzymes ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For example, DRAs were used in large quantities in the traditional naval stores industry to protect wooden ships and boats against fouling (Langenheim, 2003). In modern industrial applications, DRAs are converted into an array of biochemicals and bioproducts such as coatings, polymers, inks, flavors, and fragrances Hillwig et al, 2011;Zerbe and Bohlmann, 2015a). Conifer DRAs are of considerable structural diversity, which results from the combined activities of multienzyme families of diterpene synthases (diTPSs) and cytochrome P450 monooxygenases (P450s) in a modular biosynthetic system (Hamberger et al, 2011;Bohlmann, 2015a, 2015b).…”
mentioning
confidence: 99%
“…S1) to produce various bicyclic or, more commonly, tricyclic diterpene structures (Peters, 2010;Zerbe and Bohlmann, 2015a). Families of diTPSs, including the isopimaradiene synthases (ISO) and levopimaradiene/abietadiene synthases (LAS), have been characterized in several spruce and pine species (Martin et al, 2004;Ro and Bohlmann, 2006;Keeling et al, 2011;Zerbe et al, 2012;Hall et al, 2013b).…”
mentioning
confidence: 99%